STUDY ON SPEEDING BEHAVIOUR OF DRIVER’S MOTOR VEHICLES TO TRAFFIC ACCIDENT RISK IN NATIONAL ROAD IN MAKASSAR CITY - Muhammad Isran Ramli; Hajriyanti Yatmar; Muralia Hustim; Elvita Bellani (Traffic Accident Research Center, Indonesia Traffic Police Corps and University of Jember, 2019)
The traffic accidents often occur due to the lack of awareness while driving. The variance reason such us undisciplined and unwise to be polite when driving is the main cause of crashes. Road safety is one of the important roles to support and to develop to the commonwealth. This research aims to investigate the potential risk of speeding on a national road in Makassar. The driver performance the speeding is more occurs in the midnight till dawn. The situation of drivers while speeding is conducted to make them arrived early to the destination. The respondents' preferences also show the speed of the vehicle through the national road is around 40 – 60 km/hour. It is still in normal speed requirement at least 60 km/hour. Potensi kecelakaan akibat ketidaktertiban dalam berlalu lintas dapat terjadi. Penyebab kecelakaan lalu lintas dapat beragam seperti kurangnya kesadaran untuk berkendara secara bijak dan tertib serta penuh tanggung jawab. Pentingnya menjaga ketertiban ketertiban berkendara merupakan salah satu upaya dalam mendukung pembangunan dan integrasi nasional untuk memajukan kesejahteraan umum. Dalam melihat potensi risiko kecelakaan maka dilakukan suatu studi terkait perilaku pengendara kendaraan bermotor yang melampaui batas kecepatan pada ruas jalan di nasional di kota Makassar. Kecenderungan pengendara kendaraan bermotor yang melampaui batas kecepatan maksimum banyak terjadi pada malam hingga dini hari dengan tujuan agar pengendara sampai lebih cepat atau tepat waktu. Hasil wawancara juga menunjukkan bahwa responden mayoritas menggunakan kecepatan pada kisaran 40 – 60 km/jam dan masih masuk dalam kategori kecepatan normal dan tidak melampaui batas maksimum .